A Spontaneous dissecting posterior cerebral artery aneurysm in a 10-month-old female infant: a case report: Spontaneous dissecting posterior cerebral artery aneurysm - Aghamiri, Seyed Hossein; Salimi, Sohrab; Sepehrirad, Atefe; Sistanizad, Mohammad; Pourheidar, Elham (Iranian Journal of Child Neurology, 2022)
Posterior Cerebral Artery (PCA) aneurysms are a rare group of intracranial aneurysms. Pediatric aneurysms account for approximately 4% of all aneurysms and commonly are associated with an underlying predisposing disorder such as trauma. In contrast to traumatic aneurysms, spontaneous dissecting aneurysms are pointed out as a rare cause of pediatric aneurysms. aimed to present one case of a spontaneous dissecting aneurysm in a 10-month-old female infant.